악성 뇌종양 세포에서 quercetin과 chloroquine의 병합처리 시 유도되는 세포 사멸 기전 연구 - 이주안 (The Graduate School, Ajou University, 2014)
Since malignant gliomas are the most common brain tumor in adults, having notorious resistance to various chemotherapeutics, new therapeutic approaches are needed for more effective treatment of malignant gliomas. We show herein that quercetin, a flavonoid, and chloroquine (CQ), an antimalarial drug, synergistically induce caspase-mediated apoptosis in T98G cells. Combined treatment with quercetin and CQ accumulated poly-ubiquitinated proteins and activated unfolded protein response (UPR) in these cells. We found that combined treatment with quercetin and CQ increases intracellular and mitochondrial Ca2+ levels. The cell death by quercetin plus CQ was effectively inhibited by dantrolene (a ryanodine receptor antagonist) and RU-360 (an inhibitor of mitochondrial uniporter), suggesting that the release of Ca2+ from the endoplasmic reticulum and mitochondria Ca2+ influx may be critically involved in this cell death. In addition, combined treatment with quercetin and CQ increased ROS levels and their scavenging using N-acetylcysteine or GSH markedly inhibited the cell death by the combined treatment. Taken together, combined treatment with quercetin and CQ induces cell death via the increase of Ca2+ and ROS levels in glioma cells.
학위논문(석사)--아주대학교 일반대학원 :의생명학과,2014. 8
Keywords: Glioma; Quercetin; Chloroquine; Reactive oxygen species; Ca2+